About Mindset and Language: Or We Believe As We Pray, We Live As We Believe - Laumenskaitė, Irena Eglė; Akelaitis, Algirdas (Colloquia, 2017)
The authors of this article take an approach of hermeneutic circle in their research on the link between the historically developed Lithuanian lifestyle and mentality that define the semantics of socially actual notions, the language of Bible translations and prayers. In twentieth century translations of the New Testament into Lithuanian they find persuasive example for hermeneutic reflection in the prioritisation of the word garbė (honour), which corresponds only to the social dimension of the Greek word doxa, resulting in neglect of the word’s theological meaning, which is much more essential to Biblical thought. During the nineteenth and twentieth centuries, traditional Lithuanian mentality was impacted by the focus on defining Lithuanian identity in terms of language, which was essential to the pursuit of Lithuania’s political sovereignty. Cultural identity was determined by the peasant worldview, which drew on the semantic field of language to promote values. The influence of apprehension on Bible translation is inevitable: the lifestyle can influence the way we read and understand the Bible and similarly the choice of the words we put into our prayers. And vice versa: how we pray, read and understand the message of the Bible, we choose the lexemes for Bible translation that condition our belief and finally the lifestyle. Drawing on the principles of hermeneutics the authors of the article analyse instances of incongruence between the historical mentality of honour and the semantic field of doxa in various translations.